Analysis of Business Success of Female MSMEs in Surabaya Culinary Tourism Center - Mochamad Mochklas; Djoko Soelistya (Universitas Sebelas Maret, 2025)
Female MSME entrepreneurs in SWK Surabaya face various challenges in achieving success in business. This study aims to analyze the factors that influence the success of female Micro, Small, and Medium Enterprises (MSMEs) in the Surabaya Culinary Tourism Center (SWK). This study uses a quantitative approach, as many as 191 female MSME actors spread across SWK Surabaya were willing to be respondents, and the incoming data were analyzed using SEM-PLS. The results of the study showed that access to capital, family support, digital literacy, and work motivation each had a positive but not significant effect on business success. And business training had a significant positive effect on business success, this finding emphasizes the importance of business training in improving the performance and success of MSME actors.Keywords: business success, female MSME entrepreneurs, SWK Surabaya